Business models, value capture, and the digital enterprise - David J. Teece; Greg Linden (Journal of Organization Design, 2017)
Firms across all industries are embracing internet-based digitization strategies to expand or improve their business. In many cases, though, internet-based businesses pursue customer growth ahead of profits. The path to profitability, which is a core element of a business model, should not be an afterthought. A well-designed business model balances the provision of value to customers with the capture of value by the provider. The elements of a business model and the dynamic capabilities that help design, implement, and refine a model for an organization and its business ecosystem are reviewed. The article then translates these concepts with respect to key organizational design decisions such as that of licensing versus practicing an innovation, insourcing versus outsourcing, and building a business ecosystem.
Keywords: 650; Business model; Dynamic capabilities; Platform; Business ecosystem; Boundaries of the firm; Value capture